The Effectiveness of the Environmental Management System (EMS) Implementation in Green Supply Chain: A Case Study - Daud, Sarbani; Yusof, Nurfaizah; Mokhtar, Mazita (KnE Social Sciences, 2019)
Environmental awareness rapidly increased worldwide these recent decades. Likewise, individuals but also business organizations have begun practicing ”Green” initiatives in their organization’s operations to reduce environmental impact. The implementation of the Environmental Management System (EMS) in the Green Supply Chain (GSC) is an approach to adopt the green initiatives in the business operations that beneficial to the organization, not just regarding the environmental benefits, but economic and social as well. In an example where EMS improves the environmental performance of the organization, previous research suggests that improvements not only occur within the limits of the organizational operation but also need to be extended throughout the supply chain. The effectiveness of EMS implementation in the green supply chain boosts the environmental performance of the organization. Ultimately, EMS and GSCM practices are complementary to each other. Organizations that implemented EMS have more signs of improving the environment not only at the boundaries of their organizations but also across their network of buyers and suppliers. This research explains the debate by empirically assessing the relationship between EMS and GSCM practices.